Implementasi Augmanted Reality sebagai Media Pengenalan Sains Sederhana Pada Anak Usia Dini - Erna Erna (Ikatan Ahli Informatika Indonesia (IAII), 2018)
This study aims to determine the increasing knowledge of simple science in Early Childhood in Kindergarten-right Aisyiyah Batusangkar after using Augmanted Reality technology as learning media. The type of research conducted is classroom action research. The research methodology that used in this reasearch was mixed methodology with qualitative and quantitative approach with research subject is 20 children of group B I kindegarten. The technique used in data collection and data analysis in the form of observation and subsequent interview is processed by quantitative descriptive analysis in SPSS. This classroom action research is conducted in two cycles, namely first cycle and second cycle . The introduction of children's Science in first cycle was generally still low with the average value reaches 65 %%, then second cycle plan is revised again and The increasing reaches 99% average value, positive with an increase of 34%.